Manajemen Fisioterapi Pada Kasus Frozen Shoulder: A Case Report - Sabilla Khumairoh; Tiara Fatmarizka; Atik Hidayati (Jurnal Kesehatan dan Fisioterapi, 2022)
Frozen shoulder has a characteristic appearance with various levels and limitations of motion in the shoulder joint. The primary cause is still uncertain (idiopathic), while the secondary causes are usually due to trauma to the glenohumeral joint, postoperative glenohumeral joint surgery, prolonged immobilization, diabetes, thyroid disorders, Dupuytren's disease and other autoimmune diseases. This study uses a case report method conducted on frozen shoulder patients at Praktik Fisioterapi Mandiri Atik Hidayati Klaten in February 2022. In this case the patient experienced pain, limited Range of Motion (ROM) and decreased functional ability. Physiotherapy management given is the provision of Infra Red (IR), Transcutaneous Electrical Nerve Stimulation (TENS), Passive Joint Mobilization and Static Stretching. After 3 times of therapy, the results showed a decrease in pain, an increase in ROM in the shoulder joint and an increase in functional ability in the shoulder as measured by the Shoulder Pain and Disability Index (SPADI) index. The combination of giving IR, TENS, Passive Joint Mobilization and static stretching is effective in overcoming problems that arise due to frozen shoulder.Keywords: frozen shoulder, TENS, mobilization, static stretching